Analysis of digital marketing strategies of the @merconmerahputih account on social media in enhancing brand awareness - Prasetyo Adinugroho; Intan Tri Kusumaningtias (Universitas Nusa Cendana, 2026)
This study examines the effectiveness of digital marketing strategies in enhancing brand awareness through the social media accounts of @merconmerahputih. Adopting a qualitative case study approach, the research explores how the integration of the marketing mix contributes to building brand awareness across digital platforms. The findings demonstrate that the coordinated implementation of product, price, place, and promotion strategies effectively strengthens the three dimensions of brand awareness ; brand recognition, brand recall, and top-of-mind awareness, through consistent visual identity, interactive storytelling, and influencer-driven campaigns. Platform-specific strategies, including short-form videos and viral challenges on TikTok alongside visual storytelling and user-generated content on Instagram, generated substantial audience engagement and contributed to increased sales performance across multiple digital marketplaces. These findings highlight the importance of an integrated, platform-oriented digital marketing strategy in strengthening brand positioning and improving the competitiveness of SMEs in the digital economy. The study contributes to the growing literature on social media marketing by demonstrating how strategic integration across digital platforms can simultaneously enhance brand awareness and business performance. Keywords: Brand Awareness; Digital Marketing; SMEs; Social Media